The effect of viola odorata syrup on anxiety in postmenopausal women: A randomized clinical trial - Fatemeh Lotfi; Fatemeh Zahra Karimi; Seyed Reza Mazloum; Mahdi Yousefi; Hasan Rakhshande (Tehran University of Medical Sciences, 2021)
Background & Aim: Anxiety is one of the most important psychological problems during the menopausal period. Anxiety can affect the health and quality of life of postmenopausal women. The purpose of this study was to investigate the effect of viola odorata syrup on anxiety among postmenopausal women. Methods & Materials: This study is a triple blind clinical trial that was performed on 84 postmenopausal women referred to health centers in Mashhad in 2019. In both groups, postmenopausal women received 5 ml of viola odorata or placebo syrup twice a day for one month. Before and after the intervention, anxiety was assessed using the Depression, Anxiety and Stress scale-21. Data was analyzed using the SPSS software version 25 and Mann-Whitney, Chi-square and Fisherchr('39')s exact tests. Results: Before the intervention, there was no significant difference in women's anxiety levels between viola odorata group and placebo group, and the two groups were homogeneous (P=0.084). After the intervention, there was a significant difference between the two groups (P=0.004). The corrected average was 3.61±3.02 (2.9-4.2, CI95%) for the violet group and 7.63±3.60 (6.9-8.3, CI95%) for the placebo group. Also, after the intervention the anxiety score decreased in the viola odorata group, and increased in the placebo group. The Mann-Whitney U test showed a significant difference (P<0.001). Conclusion: According to the results of the present study, viola odorata syrup decreased anxiety in postmenopausal women. Therefore, it can be used as a complementary treatment along with chemical therapies to reduce anxiety in postmenopausal women. Clinical trial registry: IRCT20180514039660N1